Tinjauan Kriminologi Terhadap Aksi Tawuran Antar Pelajar Akibat Rivalitas Antar Sekolah : Studi Kasus di Polres Kota Pematang Siantar - Wulan Harumning; Bisdan Sigalingging (Lembaga Pengembangan Kinerja Dosen, 2024)
Brawls between students have become a phenomenon that occurs quite often in various regions of Indonesia. Brawls usually occur due to high rivalry between students from two or more schools. This rivalry often boils down to mutual attacks or physical clashes. One of the main causes of high rivalry between schools is the existence of school egos and student gangs. Student gangs in each school usually also want to show their existence and strength by making trouble. This is a form of introducing teenagers that involves students which is increasingly occurring. The research method used in this study is an empirical method that is descriptive, explaining and describing completely the situation that occurs in the community by conducting research directly in the field and analyzing the existence of behavior that deviates from the norms that are not implemented in the environment. The source of research data is in the form of primary legal materials and secondary legal materials. Data collection methods and interview techniques. Factors that affect the cause of violence between students in the city of Pematang Siantar carried out by students usually occur due to disputes between schools and other schools, lack of affection from home (parents) or from the surrounding environment, and even from the influence of friends. Another factor is the influence of social media, because this social media can be very influential and accelerate the dissemination of information and even mobilize groups. Regarding the sanctions that can be imposed on minors who commit criminal acts are in accordance with what is regulated in Law Number 12 of 2012 concerning the Juvenile Criminal Justice System, the first effort made by the Pematang Siantar Police is to seek dissolution first, Then if the child commits a minor or serious crime, the police will seek deliberation by involving the perpetrator and his parents/guardians, victims and/or parents/guardians. In this process, the police will offer diversion or peaceful efforts so that the case does not reach the court.